Meningioma pada akseptor kontrasepsi hormonal: laporan kasus - Putu Ayu Kartika Putri Saraswati; Ni Ketut Ayu Sudiariani; I Made Dommy Astika; Ni Putu Sukarini (Intisari Sains Medis, 2022)
Background: Meningiomas are the most common primary central nervous system (CNS) tumors. The incidence of meningioma is mostly found in women. There is an association between hormones and the incidence of meningioma. The symptoms of meningioma are unspecified and depend on the tumor's location. This case study aims to evaluate meningioma in the hormonal contraceptive acceptor. Case Presentation: A 36-years-old female patient was hospitalized with a chronic progressive headache that occurred for approximately two months. It was a throbbing headache in the left area of the head that worsened in the lying position. The patients deny other symptoms, such as weakness on one side of the body, nausea, vomiting, blurred visions or double visions, or convulsions. The patient had a history of receiving hormonal contraception for over 10 years. CT with contrast reveals a strong contrast enhancement, a well-defined, round-shaped lesion in the left sphenoid wing. In this case, tumor resection was done. From the histopathological examination, chordoid meningioma was found. Based on WHO grading, chordoid meningioma belongs to WHO grade II. Conclusion: The longer exposure to the exogenous progesterone injection, the lower the expression of Progesterone Receptors (PR) and mRNA Neurofibromatosis-2 (NF2) in the serum, and that lower expression of PR and NF2 was significantly and independently associated with a higher risk of females to suffer from meningioma.   Latar Belakang: Meningioma adalah tumor primer sistem saraf pusat (SSP) yang paling sering ditemukan. Insiden meningioma lebih banyak ditemukan pada wanita, dimana diduga ada keterkaitan hormon pada wanita dengan kejadian meningioma. Gejala meningioma seringkali tidak spesifik dan tergantung dari lokasi tumbuhnya tumor. Laporan kasus ini bertujuan mengevaluasi meningioma pada akseptor kontrasepsi hormonal. Presentasi Kasus: Pasien wanita berusia 36 tahun dirawat dengan keluhan nyeri kepala kronik progresif yang dialami selama kurang-lebih dua bulan. Keluhan dirasakan seperti berdenyut di kepala sebelah kiri, memberat dengan posisi berbaring. Keluhan lain seperti lemah separuh tubuh, mual, muntah, pandangan kabur atau ganda, serta kejang disangkal oleh pasien. Pasien memiliki riwayat penggunaan kontrasepsi hormonal injeksi setiap 3 bulan selama lebih dari 10 tahun. Pada pemeriksaan CT kepala dengan kontras didapatkan gambaran lesi menyangat kontras berbentuk bulat, berbatas tegas pada sphenoid wing kiri. Dilakukan reseksi tumor serta dilakukan pemeriksaan histopatologis dengan hasil chordoid meningioma, yang merupakan WHO derajat II. Simpulan: Semakin lama paparan terhadap progesteron eksogen injeksi, maka ekspresi Reseptor Progesteron (RP) dan mRNA Neurofibromatosis-2 (NF2) dalam serum akan semakin rendah yang secara signifikan dan independen berhubungan dengan risiko yang lebih tinggi bagi wanita untuk menderita meningioma.